Efektivitas Pelayanan Dokumen Kependudukan melalui Sistem Paduko - Atika Farhani; M. Fachri Adnan (Faculty of Social Science, Universitas Negeri Padang, 2021)
The purpose of this study was to determine the effectiveness of “paduko” system and the factors that affect the effectiveness of population document services through the paduko system at the Padang Panjang population and civil registration office and to determine the obstacles that occurred when implementing the paduko system in the city of Padang Panjang. This research uses qualitative research with descriptive methods carried out by purposive sampling. Data collection techniques were carried out by interview and documentation study with informants of several Padang Panjang Population and Civil Registry Offices and several people who had used paduko. Paduko is an online population document service made to make it easier for people to manage population documents with paduko being able to manage population documents anytime and anywhere as easily as shopping online without having to come directly to the population service office, but in practice there are still many people who do not understand how to use paduko, especially people who are elderly because not everyone is literate about existing technology.